D-MANNOSE TO PREVENT URINARY TRACT INFECTIONS IN MULTIPLE SCLEROSIS. Issue 12 (15th November 2016) - Panicker, Jalesh; Phé, Véronique; Pakzad, Mahreen; Haslam, Collette; Gonzales, Gwen; Curtis, Carmel; Porter, Bernadette; Chataway, Jeremy
Abstract : Introduction: Urinary tract infections (UTIs) are a significant problem in Multiple sclerosis (MS). D-mannose is a natural supplement shown recently to prevent UTIs, however benefits in multiple sclerosis (MS) are unknown. Objective: To evaluate feasibility of using D-Mannose in MS patients reporting recurrent UTIs. Methods: In this prospective single-centre, open-label study, participants were given D-mannose (Nature upplies Ltd, UK) 1.5 grams twice daily for 16-weeks and compliance recorded. Training was provided for recognising UTIs and self-monitoring using urine reagent-strip dipsticks. Results of dipsticks and cultures when UTIs were suspected, and antibiotic prescriptions, were recorded. Results: Median compliance of 22 patients (18 females; median age 50 years (46–59), (group 1 not using catheters (n=10); group 2 catheter-users (n=12)) using D-Mannose was 100%; no adverse events were reported. In total, there were 61 episodes of suspected UTIs and 29 prescriptions for antibiotics. In group 1, median number of prescriptions was 1 (0–2.2) and culture-proven symptomatic UTIs 0.5 (0–1) and in group 2, 2 (0–3) prescriptions and 1 (0–2) culture-proven UTIs. Number of monthly UTIs significantly decreased in both groups (p<0.01). Conclusion: The use of D-mannose in MS patients reporting recurrent UTIs is associated with a reduction in the number of UTIs and antibiotic prescriptions, without safety concerns. Larger studies are required to confirm efficacy.